A Better Pharmaceutical Organizational Culture for Better New Drug Performance in Thailand: Mediating Role of Organizational Sustainability Dimensions (International Journal of Psychosocial Rehabilitation, 2020)
In the past few decades, it can be seen that some organizations keen to take an effective organizational sustainability model to expand as well as to enhance the performance of their existing products through science and IT operations. However, the main purpose of this study is to enhance the performance of existing products and services through the development of positive organizational culture and environment. This research paper also aims to identify the mediating impact of organizational sustainability which future includes monitoring and evaluation, capital management, and customer-oriented management. For this intention, the analysts of this research collect data and information from about 315 respondents out of which 150 were female and 165 were male. For the purpose of data analysis and calculation of data, this research study uses structural equation modeling and the KMO technique. The results of this study revealed that positive organizational culture and environment can help an organization to enhance the performance of their existing products. The findings of this study also manifest that capital management positively effects the relationship of organizational culture with the new drug performance. Significant results of the study contribute to existing literature and also help many sectors to enhance the performance of existing products.